An etching solution for TFT-LCD panel and its application in etching a copper process panel containing a multi-layer alloy layer
By adjusting the etching liquid formula, controlling the etching cone angle and pH range, and combining the use of metal residue remover, the problems of narrow controllable etching cone angle and environmental pollution in the prior art are solved, and an efficient and environmentally friendly etching effect is achieved.
Patent Information
- Application Number
- CN202211701044.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-28
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2042-12-28
AI Technical Summary
Prior art When etching a TFT-LCD panel, the controllable range of etching cone angle is narrow, and multi-layer etching involves the use of fluorine, resulting in environmental pollution.
By adjusting the type of organic acids and the amount of corrosion inhibitor in the etching solution formula, controlling the etching cone angle, and adding acid buffer pairs and metal chelating agents to control the pH range, extending the life of the etching solution. At the same time, add metal residue remover to remove residual metal to ensure that the etching liquid is fluorine-free and green and environmentally friendly.
The controllability of the etching cone angle is achieved, the life of the etching liquid is extended, environmental pollution is avoided, and the key technical indicators of the TFT-LCD panel are met.
Smart Images

Figure CN115948745B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of wet electronic chemicals, and in particular to an etching solution for a TFT-LCD panel and application thereof in etching a copper process panel containing multiple layers of alloy. Background Art
[0002] Liquid crystal display devices have many advantages such as thin body, power saving, and no radiation, and are widely used. With the increasing demand for large-size high-definition display screens, the process technology of large-size panels is also constantly innovating. Displays represented by TFT-LCD (thin film transistor-liquid crystal display) have developed from G5 and G6 high generations to G10.5 generation lines. Usually, liquid crystal display panels include CF substrates, TFT array substrates, and liquid crystals arranged between the CF substrate and the TFT array substrate. The direction of the liquid crystal molecules is controlled by whether the TFT array substrate is powered or not, and the light of the backlight module is projected onto the CF substrate to produce a picture. The performance characteristics and operating characteristics of the TFT array substrate depend to a large extent on the materials that form the various components of the TFT array substrate. The copper process with better resistance to electromigration replaces aluminum as the gate in the liquid crystal panel. In the process of copper wire, a series of process flows such as sputtering film growth, glue coating-exposure-development, etching, etc. are required to prepare the copper circuit of the specific structure required by the liquid crystal panel, and subsequent processes such as coating of other circuit layers are carried out. When wet etching is performed with special chemicals, the metal that is not protected by the photoresist is etched away to form a circuit. However, in the process of etching the metal downward, the etching liquid will inevitably perform lateral etching. The slope angle formed by the lateral etching is called the etching cone angle. The etching cone angle size requirements of different coatings are different. If the cone angle is too large, the upper coating (the thickness is generally only a few hundred nanometers) will form a disconnection at the cone angle, making the entire product scrapped due to circuit problems; if the cone angle is too small, the electrical signal transmission performance will be poor. At the same time, when etching a multi-layer metal film layer, the etching ability in a weakly acidic solution of metals such as molybdenum, titanium or titanium alloy is poor, and the metal residue will seriously cause a circuit short circuit. It is often necessary to add fluorine to remove the residual metal, and the addition of fluorine is not friendly to the environment. In the liquid crystal panel process, the controllable range of the etching cone angle of the prior art is narrow, and multi-layer etching involves the use of fluorine. Therefore, how to meet the different positions of the circuit layer to adjust the etching cone angle accordingly, develop an etching liquid for TFT-LCD panels, and use it in etching a multi-layer copper process panel containing an alloy layer is very important. Summary of the invention
[0003] The purpose of the present invention is to solve the problems of the prior art that the controllable range of the etching cone angle is narrow, and the use of fluorine in multi-layer etching causes environmental pollution, and to provide an etching solution for TFT-LCD panels and its application in etching multi-layer copper process panels containing alloy layers. The present invention controls the size of the etching cone angle by adjusting the type of organic acid in the etching solution formula, and optimizes the amount of corrosion inhibitor to regulate the side etching ability; as the copper ion load increases, the pH continues to rise, and it is necessary to add an acidic buffer pair and a metal chelating agent to jointly control the ratio of free metal copper ions to complexed metal copper ions, thereby controlling the pH to fluctuate within a lower range, which can extend the life of the etching solution and is not easy to be scrapped. A metal residue remover is added to remove the residual metal. The etching solution of the present invention is fluorine-free and green and environmentally friendly.
[0004] To achieve the above object, the present invention adopts the following technical solutions:
[0005] The invention provides an etching solution for a TFT-LCD panel. The etching solution comprises an oxidant, an inorganic acid, an organic acid, a metal chelating agent, a metal residue remover, an acidic buffer pair, a corrosion inhibitor and water. The etching solution can control the size of the etching cone angle, has no metal residue, maintains etching stability, has a long etching life, and meets key technical indicators of etching.
[0006] The oxidant is an oxygen-containing oxidant, which includes one or more of hydrogen peroxide, ammonium persulfate, sodium persulfate, nitric acid, potassium chlorate and perchloric acid. The oxidant accounts for 5-20% of the total mass of the etching solution, preferably 8-10%.
[0007] The organic acid contains one or more carboxyl groups, including at least one of formic acid, acetic acid, propionic acid, succinic acid, oxalic acid and citric acid. The organic acid accounts for 0.1-10% of the total mass of the etching solution, preferably 2-5%.
[0008] The metal chelating agent is one of aminocarboxylic acid type and organic phosphoric acid type or a combination of the two, wherein the aminocarboxylic acid type is selected from one of ethylenediaminetetraacetic acid (EDTA), diethylaminepentaacetic acid (DTPA), nitrilotriacetic acid (NTA) and nitrilotriacetic acid, and the organic phosphoric acid type is selected from one of aminotrimethylenephosphonic acid (ATMP), hydroxyethylidene diphosphonic acid (HEDP) and ethylenediaminetetramethylenephosphonic acid (EDTMP), and the metal chelating agent accounts for 0.1-10% of the total mass of the etching solution, preferably 1-3%.
[0009] The metal residue remover is one or two of polyvinyl pyrrolidone (k15, K30 or K90), polyacrylamide (molecular weight 1000), polyethylene glycol (molecular weight 200-800) and polyethyleneimine (molecular weight <1000), and the metal residue remover accounts for 0.01-5% of the total mass of the etching solution, preferably 0.05-2%.
[0010] The acidic buffer pair is any one of the following three pairs: (1) sodium phosphate and disodium hydrogen phosphate; (2) acetic acid and sodium acetate; (3) glycine-sulfuric acid. The acidic buffer pair accounts for 0.1-5% of the total mass of the etching solution, preferably 1-2%.
[0011] The corrosion inhibitor comprises one or two of benzotriazole, mercaptobenzothiazole, 3-amino-1,2,4-triazole, 1H-tetrazole and 5-methyltetrazole, and the corrosion inhibitor accounts for 0.01-3% of the total mass of the etching solution, preferably 0.02-1%.
[0012] The pH value of the etching solution is in the range of 2.0-6.5, preferably 4.0-6.0.
[0013] The invention also provides an application of an etching solution for a TFT-LCD panel in etching a copper process panel having multiple layers containing alloy layers.
[0014] The copper process panel in the present invention is Cu / Mo or Cu / MoTi.
[0015] Compared with the existing etching solution, the present invention has the following advantages:
[0016] The single-layer or multi-layer cone angle etched by the etching solution of the present invention is controllable, the high copper powder loading solution is stable, and the life span reaches 7000ppm. The etching angle size is regulated by screening the organic acid type of the etching solution and the amount of the corrosion inhibitor; the etching stability is controlled and the etching life is extended by screening the acidic buffer pair and the metal chelating agent. The metal residue remover can remove the residue of molybdenum, titanium or titanium alloy without undercutting, thereby meeting the important parameter index requirements of the panel display.
[0017] The present invention regulates the etching speed of the copper layer by different organic acids and corrosion inhibitors, and the buffer and the metal chelating agent work together to control the etching cone angle to switch between 30-40°, 40-50°, 50-60°, and 60-70°; a metal residue remover is added to remove the residual metal, and the etching solution is fluorine-free and green and environmentally friendly. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 It is a schematic diagram of the cross-sectional structure of the TFT-LCD Cu / Mo copper process panel;
[0019] Figure 2is a scanning electron microscope image using formic acid in Example 1 of the present invention;
[0020] Figure 3 is a scanning electron microscope image of acetic acid used in Example 1 of the present invention;
[0021] Figure 4 is a scanning electron microscope image of propionic acid used in Example 1 of the present invention;
[0022] Figure 5 is a scanning electron microscope image of succinic acid used in Example 1 of the present invention;
[0023] Figure 6 is a scanning electron microscope image of citric acid used in Example 1 of the present invention;
[0024] Figure 7 is a cross-sectional view of the sample after etching observed under a scanning electron microscope in Example 4 of the present invention;
[0025] Figure 8 These are the SEM images in Table 3 of Example 3 of the present invention. DETAILED DESCRIPTION
[0026] In order to better understand the present invention, the applicant will further describe the present invention in detail below.
[0027] The cross-sectional structure diagram of the TFT-LCD Cu / Mo copper process panel of the present invention is shown in the attached Figure 1 , wherein the bottom layer is a glass layer, the middle layer is a Cu / Mo metal layer, the upper layer is an ITO layer, and the outermost layer is a photoresist. Specific operation: prepare etching solutions according to the following embodiments 1-3 respectively, and then immerse Cu / Mo or Cu / MoTi copper process panels of different thicknesses in the etching solutions respectively, take them out after 90 seconds, wash them with water, blow dry them, spray platinum, and observe them under a Hitachi S-4700 field emission scanning electron microscope. The Cu / Mo and Cu / MoTi copper process panels in the following embodiments are all produced by Shenzhen Huaxing Optoelectronics Co., Ltd., wherein the thickness of the copper layer in the Cu / Mo copper process panel is 3000A, and the thickness of the molybdenum layer is 300A; the thickness of the copper layer in the Cu / MoTi copper process panel is 8000A, and the thickness of the molybdenum-titanium layer is 300A.
[0028] Example 1
[0029] Prepare etching solution, the total mass of etching solution is 100g, add 40g of hydrogen peroxide with a mass fraction of 30%, 2g of organic acid, 0.8g of ATMP and 0.7g of ethylenediaminetetraacetic acid (EDTA) as metal chelating agent, 0.7g of sodium phosphate and 0.8g of disodium hydrogen phosphate as pH buffer, 0.5g of benzotriazole as corrosion inhibitor, about 0.1g of sulfuric acid with a mass fraction of 50% to adjust the pH of the solution, 0.05g of polyacrylamide (molecular weight 1000), and then add water to make up to 100g, stir for 30 minutes, and the pH meter detects that the pH of the etching solution prepared above is 4.0. Different etching solutions obtained after adding different organic acids, the Cu / Mo copper process panel is immersed in the following etching solutions respectively, taken out after 90 seconds, washed with water, blown dry, sprayed with platinum, observed under Hitachi S4700 scanning electron microscope, and the following Table 1 is obtained.
[0030] Table 1
[0031]
[0032] It can be seen from Table 1 above that different organic acids have different etching angles on the Cu / Mo copper process panel. In this way, the appropriate organic acid can be selected to prepare the etching solution according to the requirements of the key technical indicators of the etching panel.
[0033] Example 2
[0034] Prepare the etching solution components, the total mass of the etching solution is 100g, add 40g of hydrogen peroxide with a mass fraction of 30%, 2g of citric acid, add metal chelator ①1g, metal chelator ②1g, then add 0.7g of sodium phosphate and 0.8g of disodium hydrogen phosphate as pH buffer, add 0.5g of benzotriazole as corrosion inhibitor, 0.05g of polyacrylamide (molecular weight of 1000), 0.2g of sulfuric acid with a mass fraction of 50% to adjust the pH of the solution, then add water to make up to 100g, stir for 30 minutes, and the pH of the etching solution prepared above is detected by pH meter as shown in Table 2 below. Different etching solutions obtained after adding different metal chelators, the Cu / Mo copper process panels are immersed in the following etching solutions respectively, taken out after 90 seconds, washed with water, blown dry, sprayed with platinum, observed under Hitachi S4700 scanning electron microscope, and the following Table 2 is obtained.
[0035] Table 2
[0036]
[0037] It can be seen from Table 2 above that different metal chelating agents have an impact on the life of the etching solution, and the two chelating agents coordinate with each other to achieve a higher etching stability life and reduce the cost of the etching solution.
[0038] Example 3
[0039] Prepare the components of the etching solution. The total mass of the etching solution is 100g. Add 40g of hydrogen peroxide with a mass fraction of 30%, 2g of propionic acid, 0.5g of metal chelating agent nitrilotriacetic acid and 1.0g of ATMP in sequence, then add 0.7g of sodium phosphate and 0.8g of disodium hydrogen phosphate as a pH buffer pair, add 0.5g of benzotriazole as a corrosion inhibitor, add 0.05g of metal residue remover, 0.1g of sulfuric acid to adjust the pH of the solution, and then add water to make up to 100g, stir for 30 minutes, and the pH of the above-prepared etching solution is detected by a pH meter. See Table 3 below. Different etching solutions obtained after adding different metal residue removers, Cu / MoTi and Cu / Mo copper process panels are immersed in the following etching solutions respectively, taken out after 90 seconds, washed with water, blown dry, sprayed with platinum, and observed under a Hitachi S4700 scanning electron microscope to obtain the following Table 3.
[0040] Table 3
[0041]
[0042] It can be seen from Table 3 that after the three metal residue removers were added, no bottom metal molybdenum residue remained.
[0043] Example 4
[0044] Prepare the etching solution components. The total mass of the etching solution is 100g. Add 40g of hydrogen peroxide with a mass fraction of 30%, 2g of propionic acid, 0.5g of metal chelating agent nitrilotriacetic acid and 1.0g of ATMP in sequence, then add 0.7g of sodium phosphate and 0.8g of disodium hydrogen phosphate as pH buffer, add 0.5g of corrosion inhibitor, add 0.05g of metal residue remover, and then add water to make up to 100g, stir for 30 minutes, and the pH of the above-prepared etching solution is detected by pH meter, see Table 4 below. Different etching solutions obtained after adding different corrosion inhibitors, the Cu / Mo or Cu / MoTi copper process panels are immersed in the following etching solutions respectively, taken out after 90 seconds, washed with water, blown dry, sprayed with platinum, observed under Hitachi S4700 scanning electron microscope, and the following Table 4 is obtained.
[0045] Table 4
[0046] Corrosion Inhibitor CD Loss Benzotriazole <1μm 5-Methyltetrazolyl <1μm 3-Amino-1,2,4-triazole <1μm Mercaptobenzothiazole >1μm
[0047] Table 4 above shows that different corrosion inhibitors have different effects on CD loss, and suitable corrosion inhibitors can be selected to prepare etching solution according to the requirements of key technical indicators of etching panels.
[0048] Embodiment 5-10
[0049] In order to further illustrate the coordination between the components and adjust the proportions, an etching solution that meets multiple key technical indicators can be prepared, which is specifically described in Examples 5-10 below.
[0050] Prepare the etching solution components. The total mass of the etching solution is 100g. Add 30% hydrogen peroxide, propionic acid (organic acid), nitrilotriacetic acid and ATMP (metal chelator, the mass ratio of nitrilotriacetic acid and ATMP is 1:1) in the following proportions, then add sodium phosphate and disodium hydrogen phosphate (buffer pair), add 5-methyltetrazole (corrosion inhibitor), add polyvinyl pyrrolidone k30 (metal residue remover), add sulfuric acid to adjust the pH of the solution, add water to make up to 100g, stir for 30 minutes, and the pH of the above-prepared etching solution is detected by pH meter. See Table 5 below. Obtain etching solutions of different proportions, immerse the Cu / Mo copper process panels in the following etching solutions respectively, take them out after 90 seconds, wash them with water, blow dry them, spray platinum, and observe them under Hitachi S4700 scanning electron microscope to obtain the following Table 5.
[0051] Table 5
[0052]
[0053]
[0054] Table 5 compares the effects of different component ratios of Examples 5-10 on the key technical indicators of etching. The increase in hydrogen peroxide content has a certain effect on the angle; the increase in the amount of organic acid and the change in pH will also reduce the etching angle; the amount of corrosion inhibitor also needs to be appropriate. Too much will result in too little CD loss in etching.
[0055] The cross section of the etched Cu / Mo copper process panel sample was observed under a scanning electron microscope. The obtained figure is shown in the attached figure. Figure 7 , etching angle is 40°, and CD loss is <1μm.
Claims
1. An etching solution for etching a multi-layer TFT-LCD copper process panel containing an alloy layer, wherein the TFT-LCD copper process panel is Cu / Mo or Cu / MoTi, characterized in that: The etching solution comprises an oxidant, an inorganic acid, an organic acid, a metal chelating agent, a metal residue remover, a buffer, a corrosion inhibitor and water; The oxidant is an oxygen-containing oxidant, and the oxygen-containing oxidant includes one or more of hydrogen peroxide, ammonium persulfate, sodium persulfate, nitric acid, potassium chlorate and perchloric acid, and the mass fraction of the oxidant in the etching solution is 5-20%; The organic acid includes one or more of formic acid, acetic acid, propionic acid, succinic acid, oxalic acid and citric acid, and the mass fraction of the organic acid in the etching solution is 0.1-10%; The metal chelating agent is a combination of an aminocarboxylic acid type and an organic phosphoric acid type, wherein the aminocarboxylic acid type is selected from one of ethylenediaminetetraacetic acid (EDTA), diethylaminepentaacetic acid (DTPA), nitrilotriacetic acid (NTA) and nitrilotriacetic acid, and the organic phosphoric acid type is selected from one of aminotrimethylenephosphonic acid (ATMP), hydroxyethylidene diphosphonic acid (HEDP) and ethylenediaminetetramethylenephosphonic acid (EDTMP), and the metal chelating agent accounts for 0.1-10% of the total mass of the etching solution; The metal residue remover is one or two of polyvinyl pyrrolidone, polyacrylamide with a molecular weight of 1000, polyethylene glycol 200-800 and polyethyleneimine with a molecular weight of less than 1000; the metal residue remover accounts for 0.01-5% of the total mass of the etching solution; The buffer pair is sodium phosphate and disodium hydrogen phosphate; the buffer pair accounts for 0.1-5% of the total mass of the etching solution; The corrosion inhibitor includes one or two of benzotriazole, mercaptobenzothiazole, 3-amino-1,2,4-triazole, 1H-tetrazole and 5-methyltetrazole, and the mass fraction of the corrosion inhibitor in the etching solution is 0.01-3%; The inorganic acid adjusts the pH value of the etching solution to a range of 2.0-6.
5.
2. The etching solution according to claim 1, characterized in that: The mass fraction of the oxidant in the etching solution is 8-10%.
3. The etching solution according to claim 1, characterized in that: The mass fraction of the organic acid in the etching solution is 2-5%.
4. The etching solution according to claim 1, characterized in that: The mass fraction of the metal chelating agent in the etching solution is 1-3%.
5. The etching solution according to claim 1, characterized in that: The mass fraction of the metal residue remover in the etching solution is 0.05-2%.
6. The etching solution according to claim 1, characterized in that: The mass fraction of the buffer pair in the etching solution is 1-2%.
7. The etching solution according to claim 1, characterized in that: The mass fraction of the corrosion inhibitor in the etching solution is 0.02-1%.
8. The etching solution according to claim 1, characterized in that: The pH value of the etching solution ranges from 4.0 to 6.
0.
9. Use of the etching solution according to any one of claims 1 to 8 in etching a copper process panel having multiple layers containing alloy layers.
10. The use according to claim 9, characterized in that: The copper process panel is Cu / Mo or Cu / MoTi.
Citation Information
Patent Citations
Multilayer-film etchant, concentrated etchant, and etching method
CN105765107A
Etching solution for copper / molybdenum film layer and application thereof
CN107858685A
Method for recovering phosphoric acid from waste aluminum etching liquid
CN113292056A